Evaluasi Distribusi Air Bersih dengan Menggunakan Metode Hazen William dan Hardy Cross (Studi Kasus Asrama Putra Pondok Pesantren Al-Kautsar) - Olivia Hutasoit, Eva; Dwi Yulianto, Fredi (Universitas Sulawesi Tenggara, 2024)
The Al-Kautsar Islamic Boarding School's Boys' Dormitory is a 3-storey building and there are problems with the distribution of clean water, namely the water supply that cannot meet its users when it is used during peak hours. This study aims to evaluate the distribution of clean water and provide recommendations. In this study the method used was the calculation of Hazen William and Hardy Cross using SNI 03-7065-2005 reference regarding procedures for designing plumbing systems and SNI 8153:2015 concerning pipe systems in buildings. Then the results that have been obtained from the calculation that the need for clean water is 29.4 ????3/day, for its availability of 502,400 m3, the need for clean water is not sufficient for its users. So it must be necessary to evaluate according to ideal conditions. As well as for the evaluation itself, namely the enlargement of the diameter of the 2nd floor pipe by 1